Pengaruh Kepemimpinan terhadap Kepuasan Kerja dan Komitmen Organisasi - Naya Dita Chairunnisa; Alawiyah Alawiyah; Aos Kuswandi (Global Leadership Organizational Research in Management, 2025)
This study is motivated by the high competition and complexity whitin organizations, underscoring the vital role of leadership in fostering a productive work environment, as well as the significance of job satisfaction and organizational commitment in supporting overall success. The objective of this research is to examine the influence leadership on both job satisfaction and organizational commitment trough a relevant literature review. The method employe dis a deskriptive qualitative literature review. Literture was acquired via Google Scholar from 2015 until 2025 using relevant keyword, the analyzed thematically. The findings indicate that leadership significantly and positively influences both the enhancement of job satisfaction and the formation of organizational commitment. Effective leadership, such as the ability to provide solutions, recognition, supervision, and involve employees in decision-making, demonstrably increases employee satisfaction and loyalty. Overall, strong leadership is a crucial prerequisite for cultivating job satisfaction and building solid organizational commitment, serving as a foundation for achieving organizational objectives. This study contributes to understanding the relationship among these three variables, given the limited research simultaneously examining leadership, job satisfaction, and organizational commitmen whitin a single literature review.